Sistema de registro de señales fotopletismográficas para la medición de la presión arterial y la frecuencia cardíaca - Martínez-Duque, Eduardo; Daza-Santacoloma, Genaro (Revista Científica, 2026)
This article describes the design of a photoplethysmographic signal recording system that allows measuring heart rate and blood pressure using near-infrared spectroscopy. This technique relies on the emission of infrared light, which is absorbed by human body tissues to model changes in blood volume during the cardiac cycle. The methodology includes the construction of an electronic recording circuit, the preprocessing of photoplethysmographic signals (PPG - Photoplethysmography), and the implementation of estimation algorithms. The recording circuit consists of filtering and amplification stages, while preprocessing attenuates power line interference and corrects baseline drift to improve estimation accuracy. For heart rate estimation, the algorithm automatic multiscale-based peak detection achieved a mean absolute error (MAE) of 5.22 and a mean absolute percentage error (MAPE) of 7.02%. For blood pressure estimation, low average errors were obtained, particularly for diastolic pressure (ME = 2.56, MAPE = 3.56%, and RMSE = 6.53). Graphical analysis revealed regression toward the mean and variability depending on the physiological range. It is concluded that the system demostrates adecuate performance for population level trend monitoring, although it does replace individual clinical measurement.